Pengukuran Usability Aplikasi E-Kinerja Menggunakan Metode USE Questionnaire: Study Kasus : Bakesbangpol - Rizthy Shavna Azizah; Wafiah Murniati (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
In today's digital era, almost all parts of human life depend on the development of information and communication technology, which helps in increasing efficiency, effectiveness and cost savings in various activities. The role of information and communication technology is very vital in human life today. The National and Political Unity Agency (BAKESBANGPOL) is a government agency which has the main task of social and political development in the Central Lombok Regency area. BAKESBANGPOL has implemented a system or application called e-Kinerja. The implementation of the e-Kinerja application is said to be running quite well and is easy to use, however the e-Kinerja Application also often experiences problems such as frequent human errors and lack of socialization of the e-Kinerja Application which will have an impact on decreasing efficiency and decreasing trust in the system. Therefore, measurements of application quality need to be carried out. This research aims to measure the level of usability using the USE Questionnaire method in the e-Kinerja application. This research uses quantitative research with stages of observation and interviews, preparation of questionnaires, distribution of questionnaires. The results of this research are the results of calculating the usability measurement of e-Kinerja, which obtained a value of 81.45% which is in the range of 81-100, where the e-Kinerja application at BAKESBANGPOL Central Lombok Regency is very suitable for use by ASN.